2020
DOI: 10.1111/ijfs.14780
|View full text |Cite
|
Sign up to set email alerts
|

End‐user preferences for plantain food products in Nigeria and implications for genetic improvement

Abstract: Plantain is an important food security crop for farming households in Nigeria. This study investigates the relative importance of plantain food products and their quality descriptors from the perspective of farmers in Southern-Nigeria, to inform end-user oriented and socially inclusive breeding strategies that drive hybrid adoption. Surveys were conducted in twelve rural communities in three states in the plantain belt of Nigeria, consisting of key informant interviews, sex-disaggregated focused group discussi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 27 publications
(36 reference statements)
1
19
0
Order By: Relevance
“…For example, women play an important role in cassava production (Curran et al, 2009;Walker et al, 2014), and perform most of its processing and marketing in Nigeria (Ilona et al, 2017). In the South East and South South regions of Nigeria, women play an important role in cassava production, shifting away from a formerly yam dominant cropping system and as men increase their engagement in non-farm activities (Korieh, 2010;Osuji et al, 2017;Alozie, 2019;Amah et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For example, women play an important role in cassava production (Curran et al, 2009;Walker et al, 2014), and perform most of its processing and marketing in Nigeria (Ilona et al, 2017). In the South East and South South regions of Nigeria, women play an important role in cassava production, shifting away from a formerly yam dominant cropping system and as men increase their engagement in non-farm activities (Korieh, 2010;Osuji et al, 2017;Alozie, 2019;Amah et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In Cameroon, groundnut and meat might be added during boiling; therefore, no food accompaniments are required, while plantain porridge in Nigeria is frequently eaten with beans, vegetables, meat, and stews. However, Amah et al [24] reported that porridge is more important in the South-South than in Nigeria's South-West.…”
Section: Consumption and Cooking Methods Of Plantainmentioning
confidence: 99%
“…Concerning taste, this finding was also in line with the choice of experiments of Hoek et al [48], who found that when consumers find taste very important, they will not compromise and respond to price or other measures. A study of Amah et al [24] found that most Nigerian respondents identified food quality characteristics related to color, texture, taste, and odor as the most important quality characteristics of plantain products.…”
Section: Factors Influencing Consumer's Choice and Their Willingness To Purchase New Plantain-based Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plantains are a multipurpose crop with great processing potential and a source of starch and energy in sub-Saharan Africa (SSA) [1]. They are rich in nutrients such as dietary fiber, minerals (potassium, phosphorus, calcium, sodium, and magnesium), vitamins (A and C), and phenolic compounds (carotenoids and flavonoids) [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%